2017
DOI: 10.1097/jcn.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

The Self-care Educational Intervention for Patients With Heart Failure

Abstract: This study evaluates the effectiveness of a targeted multimedia educational intervention. Study results may inform the design of in-hospital education for HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Details regarding the patient recruitment, sample size, randomisation process, theoretical framework, education intervention and participant follow-up have been described in our previously published protocol paper. 24 Briefly, blinded randomisation using a computer-generated sequence and concealed envelopes allocated participants on a 1:1 basis to usual care or multimedia educational intervention. The intervention guided by andragogy began with a needs assessment to determine the individual participant's learning needs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details regarding the patient recruitment, sample size, randomisation process, theoretical framework, education intervention and participant follow-up have been described in our previously published protocol paper. 24 Briefly, blinded randomisation using a computer-generated sequence and concealed envelopes allocated participants on a 1:1 basis to usual care or multimedia educational intervention. The intervention guided by andragogy began with a needs assessment to determine the individual participant's learning needs.…”
Section: Methodsmentioning
confidence: 99%
“…These resources were specifically developed for people with HF 25 and are described in detail in our previous publication. 24 The intervention was concluded using the teach-back approach to evaluate understanding of the main concepts. Participants were provided with a copy of the DVD and manual to use as learning resources at home.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have highlighted the importance of patient education in promoting adherence to the treatment plan and self-care recommendations. 13,14 In addition to providing education, for an intervention to be effective it is also necessary to consider the role of psychosocial factors in influencing behaviours and to address barriers that hinder behavioural changes. Therefore, the intervention needs to be multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Engagement of patients and their families in HF education and self-management support has also been proven successful in reducing readmissions 26. Multiple studies have shown that providing patients with tools to manage their disease can have a direct effect on hospital admissions 27 28. This QI involved active engagement of patients with physicians and nursing staff.…”
Section: Discussionmentioning
confidence: 99%